A prior history of binge-drinking increases sensitivity to the motivational valence of methamphetamine in female C57BL/6J mice. (January 2020) - Sern, Kimberly R.; Fultz, Elissa K.; Coelho, Michal A.; Bryant, Camron D.; Szumlinski, Karen K.
Methamphetamine (MA) and alcohol use disorders exhibit a high degree of co-morbidity and sequential alcohol-MA mixing increases risk for co-abuse. Recently, we reported greater MA-conditioned reward in male C57BL/6J mice with a prior history of binge alcohol-drinking (14 days of 2-hour access to 5, 10, 20 and 40% alcohol). As female mice tend to binge-drink more alcohol than males and females tend to be more sensitive than males to the psychomotor-activating properties of MA, we first characterized the effects of binge-drinking upon MA-induced place-conditioning (four pairings of 0.25, 0.5, 1, 2, or 4 mg/kg IP) in females and then incorporated our prior data to analyze for sex differences in MA-conditioned reward. Prior binge-drinking history did not significantly affect locomotor hyperactivity or its sensitization in female mice. However, the dose-response function for place-conditioning was shifted to the left of water-drinking controls, indicating an increase in sensitivity to MA-conditioned reward. The examination of sex differences revealed no sex differences in alcohol intake, although females exhibited greater MA-induced locomotor stimulation than males, irrespective of their prior drinking history. No statistically significant sex difference was apparent for the potentiation of MA-conditioned reward produced by prior binge-drinking history. If relevant to humans, these data argue that both males and females with a prior binge-drinking history are similarly vulnerable to MA abuse and it remains to be determined whether or not the neural substrates underpinning this increased vulnerability reflect common or sex-specific adaptations in reward-related brain regions.